Measurement of W± and Z-boson production cross sections in pp collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (Physics letters, 2016)
Measurements of the W±→ℓ±ν and Z→ℓ+ℓ− production cross sections (where ℓ±=e±,μ±) in proton-proton collisions at s=13 TeV are presented using data recorded by the ATLAS experiment at the Large Hadron Collider, corresponding to a total integrated luminosity of 81 pb−1. The total inclusive W±-boson production cross sections times the single-lepton-flavour branching ratios are σW+tot=11.83±0.02 (stat)±0.32 (sys)±0.25 (lumi) nb and σW−tot=8.79±0.02 (stat)±0.24 (sys)±0.18 (lumi) nb for W+ and W−, respectively. The total inclusive Z-boson production cross section times leptonic branching ratio, within the invariant mass window 66<mℓℓ<116 GeV, is σZtot=1.981±0.007 (stat)±0.038 (sys)±0.042 (lumi) nb. The W+, W−, and Z-boson production cross sections and cross-section ratios within a fiducial region defined by the detector acceptance are also measured. The cross-section ratios benefit from significant cancellation of experimental uncertainties, resulting in σW+fid/σW−fid=1.295±0.003 (stat)±0.010 (sys) and σW±fid/σZfid=10.31±0.04 (stat)±0.20 (sys). Theoretical predictions, based on calculations accurate to next-to-next-to-leading order for quantum chromodynamics and to next-to-leading order for electroweak processes and which employ different parton distribution function sets, are compared to these measurements.
*The ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, A.E. Baas, O. Brandt, J.I. Djuvsland, M. Dunford, D.E. Ferreira de Lima, M.P. Geisler, M. Giulini, P. Hanke, J. Jongmanns, E.-E. Kluge, M. Kolb, M. Kretz, A. Kugel, V.S. Lang, M. Lisovyi, K. Meier, H. Meyer zu Theenhausen, D.I. Narrias Villar, V. Radescu, M. Sahinsoy, S. Schaetzel, V. Scharf, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, P. Starovoitov, S. Suchek, M. Wessels [und 2818 weitere Personen]
Im Titel sind die Zeichen "+" und "-" hochgestellt
Im Titel ist [Zeta] als griechischer Buchstabe dargestellt
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 02.06.2020